The Value Chain Analysis of Coffee Products in the Case of Bandung District - Herdiani, Leni; Jamaludin, Maun; Rizkinita, Melinda Aprilia; Sudirman, Iman; Rohimat, Ismet (Almana : Jurnal Manajemen dan Bisnis, 2024)
Coffee, a significant plantation product, holds vast opportunities in both domestic and global markets. Bandung Regency is renowned for its distinctive fruit-flavored coffee, particularly from Ciwidey and Puntang, where coffee is marketed in cherry and green bean forms without branding. A value chain analysis is essential to enhance the coffee industry's added value and sustainability. This study aims to identify the coffee value chain in Bandung Regency, analyze the cost of production, total revenue, and profit of the coffee processing industry in Ciwidey and Puntang, and determine the added value of coffee products in these areas. Using descriptive analysis, results indicate that Ciwidey (MS Coffee) has a lower cost of goods produced than Puntang (Acs Siliwangi) due to higher production volumes in Puntang leading to higher costs. However, Puntang’s larger production volume also generates higher monthly revenue and profit due to a higher selling price per kilogram. Value-added analysis reveals that Puntang’s value-added per kilogram (Rp. 55,025.00/kg) surpasses that of Ciwidey (Rp. 44,647.00/kg), attributed to higher selling prices, superior product quality, and greater market presence in Puntang. Conversely, higher input prices in Ciwidey result in lower value-added.